2018
DOI: 10.7759/cureus.2575
|View full text |Cite
|
Sign up to set email alerts
|

Retained Intra-uterine Foetal Bones Resulting in Secondary Infertility: A Case Report

Abstract: Termination of pregnancy (abortion) is a reasonably safe procedure when properly performed. However, even after being performed with due precautions, complications may occur. Retention of fetal products following a mid-trimester abortion is a rare complication of abortion which can then result in secondary infertility. We are here presenting the case of a young woman who underwent an abortion in the 15th week of gestation due to anencephaly in the fetus and who then failed to conceive for the next five years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…This case highlights the difficulty in diagnosing the cause of secondary infertility and abdominal discomfort by noting that the first ultrasound scan as well as the MRI scan did not show any foreign bodies inside the endometrium. Potential differential diagnoses may include osseous metaplasia driven by chronic inflammation causing dystrophic calcification, 3 endometrial ossification driven by chronic inflammation, and tissue destruction in the mature endometrial stroma 4 . These two differential diagnoses can be ruled out because the segment retrieved by hysteroscopy looked like a fetal long bone, and the histology showed dead bone fragments but no active tissue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This case highlights the difficulty in diagnosing the cause of secondary infertility and abdominal discomfort by noting that the first ultrasound scan as well as the MRI scan did not show any foreign bodies inside the endometrium. Potential differential diagnoses may include osseous metaplasia driven by chronic inflammation causing dystrophic calcification, 3 endometrial ossification driven by chronic inflammation, and tissue destruction in the mature endometrial stroma 4 . These two differential diagnoses can be ruled out because the segment retrieved by hysteroscopy looked like a fetal long bone, and the histology showed dead bone fragments but no active tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is similar to that of an Intrauterine Contraceptive Device (IUCD) in situ. Some research has suggested that the fetal bone may have a direct toxic effect on the developing embryo, thereby causing infertility 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations